Women’s rights according to Sisters in Islam (SIS)’S understanding: an analysis from an Islamic perspective - Kamaruddin, Zuraidah; Tengku Muda, Tengku Fatimah Muliana; Mohd Yunus, Saidatolakma; Abdul Rahim, Adibah; Embong, Rahimah (Research Institute for Islamic Product and Malay Civilization (INSPIRE) Universiti Sultan Zainal Abidin (UniSZA), 2017)
Sister In Islam (SIS) is a Non-Governmental Organisation (NGO) that claimed among its objectives is to uphold Muslim women’s rights as they believe that there are certain Islamic Family laws which are implemented in the Shariah Court in Malaysia are discriminatory against women. Since SIS claims that the group was formed to understand the status of women in Islam in their aim to attain women’s rights as stipulated in Islam, the study will analyse SIS’s understanding on women’s right from an Islamic perspective. The study found that there are several misunderstandings by SIS related to women’s right as they do not apply the proper method in understanding the Qur’an. SIS has also to refer to Hadis in their discussions and their use of logic should be parallel with Islamic teachings. The findings of study will reveal the true understanding of Muslim women’s rights from an Islamic perspective to the society. Keywords: Sisters In Islam; women’s rights; Muslim thoughts; Islamic perspective